A matemática como ciência e o uso da calculadora no seu ensino - (:unkn) unknown (Universidade Federal de Goiás, 2018)
Mathematics is a science present in the lives of all people, everywhere in situations of their daily lives, whether at home, at leisure or at work. This science has evolved since man appeared on the planet until the present day, being used by the human being so that he can develop different types of activity. In the history of the development of this discipline, several technologies were created to aid in mathematical calculations, as in the case of calculators. This technology, however, is aimed at several debates, as there are those who defend its use in the classroom and there are those who are totally against this feature. Faced with this question, this research intends to analyze the use of the calculator in the teaching of mathematics. The methodological resource used for the elaboration of the research was the bibliographical review, based on works by authors who have already discussed the problematic in question. Subsequently, an analysis of two lesson plans was carried out, one for secondary education and another for the second phase of elementary school, in order to consider how the calculator could be used for the development of different types of activities within this discipline. As final considerations of the research, it is necessary to mention that the calculator can help in the development of students' calculations ability, especially because it is the student who will direct how the calculations are done and, therefore, also have to reflect on them.
Mathematics as science and the use of the calculator in their teaching
Keywords: Aluno; Aprendizagem em matemática; Ensino de matemática; Uso da calculadora; Mathematics teaching; Using the calculator; Student; Learning in Mathematics; CIENCIAS EXATAS E DA TERRA::MATEMATICA